2011
DOI: 10.3727/096368911x565038b
|View full text |Cite
|
Sign up to set email alerts
|

Implantation of Sinoatrial Node Cells into Canine Right Ventricle: Biological Pacing Appears Limited by the Substrate

Abstract: Biological pacing has been proposed as a physiologic counterpart to electronic pacing, and the sinoatrial node (SAN) is the general standard for biological pacemakers. We tested the expression of SAN pacemaker cell activity when implanted autologously in the right ventricle (RV). We induced complete heart block and implanted electronic pacemakers in the RV of adult mongrel dogs. Autologous SAN cells isolated enzymatically were studied by patch clamp to confirm SAN identity. SAN cells (400,000) were injected in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 25 publications
0
8
0
2
Order By: Relevance
“…Proof of concept has been provided using a variety of approaches to increased inward current or decreased repolarising current as a basis for propagation of a pacemaker potential [8]. In this arena of research, both embryonic stem cells and human mesenchymal stem cells have been the main area of focus, although other cell sources (skeletal myoblasts; fibroblasts; cardiac stem cells) have been utilised.…”
Section: Cell-based Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Proof of concept has been provided using a variety of approaches to increased inward current or decreased repolarising current as a basis for propagation of a pacemaker potential [8]. In this arena of research, both embryonic stem cells and human mesenchymal stem cells have been the main area of focus, although other cell sources (skeletal myoblasts; fibroblasts; cardiac stem cells) have been utilised.…”
Section: Cell-based Therapiesmentioning
confidence: 99%
“…Ischaemia converts conducting tissue into an electrically inactive scar, forcing the wave front into a region of slowconducting tissue, creating an environment suitable for reentry [2,7]. Fibrosis occurs in pacemaker cells as part of the aging process, resulting in bradycardia [8].…”
Section: Introductionmentioning
confidence: 99%
“…6567 In yet another proof-of-principle experiments, autologous SAN pacemaker cells were harvested, then transplanted back into the same animal in a dog model of sinus disorders for rhythm regeneration. 68 …”
Section: Electronic Pacemakers For Heart Rhythm Disordersmentioning
confidence: 99%
“…Human Mesenchymal Stem Cells (hMSC) are multipotent stromal cells, which can be isolated from various sources, such as the umbilical cord, amniotic fluid, dental pulp, adipose tissue, etc. Brown adipose tissue has also been found to be a good source of mesenchymal stem cells [22]. They are a suitable candidate, being relatively immunopriveleged and expressing two cardiac gap junction proteins, connexins 40 and 43 [28].…”
Section: Cell-based Approachmentioning
confidence: 99%
“…It was shown that it is possible to use CD 166 expression to select SAN precursor cells [20]. However, attempts to autologously graft the SAN or inject the myocytes failed to provide sustained biological pacemaker activity [21,22]. Instead, human Embryonic Stem Cells (hESC) derived myocytes were studied as the source of cells for creating biological pacemakers.…”
Section: Cell-based Approachmentioning
confidence: 99%